1987
DOI: 10.1016/0165-7992(87)90010-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of methods for the estimation of mutation rates in cultured mammalian cell populations

Abstract: A systematic comparison of 5 different statistical methods for the estimation of mutation rate (mu) in cultured Chinese hamster V79 cells is presented. Fluctuation tests were performed with several large batches of parallel cell cultures each allowed to grow for a different length of time in order to reach different population size (Nt). Based on Lea and Coulson's theoretical distribution, a comparison has been made between the experimental data and the expected distribution of the number of ouabain-resistant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1991
1991
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Furthermore, the observed rate of phenotypic reversion tends to vary tremendously as a function of the specific site of mutation within a gene due to "DNA context effects" (5). In the present study, use of direct selection facilitated large-scale fluctuation tests and their analysis by the maximum-likelihood method, which represents the most accurate and statistically efficient strategy widely used to measure mutation rates in microorganisms (15,17). The growth capabilities of S. acidocaldarius also facilitated efforts to directly estimate the possible impact of differential growth rates and phenotypic lag on mutation rate determinations (5).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the observed rate of phenotypic reversion tends to vary tremendously as a function of the specific site of mutation within a gene due to "DNA context effects" (5). In the present study, use of direct selection facilitated large-scale fluctuation tests and their analysis by the maximum-likelihood method, which represents the most accurate and statistically efficient strategy widely used to measure mutation rates in microorganisms (15,17). The growth capabilities of S. acidocaldarius also facilitated efforts to directly estimate the possible impact of differential growth rates and phenotypic lag on mutation rate determinations (5).…”
Section: Discussionmentioning
confidence: 99%
“…The FA-resistant (FA r ) or 6TG-resistant colonies were fixed with Carnoy's solution, stained with crystal violet, and counted. Mutation rate was calculated by the P 0 method as described (12,13) and corrected for colony forming efficiency. Rates are presented per cell per generation.…”
Section: Methodsmentioning
confidence: 99%
“…The asterisk indicates that no spontaneously arising Hprt mutants were detected (mutation frequency Ͻ10 Ϫ8 ). (b) Preexisting APRT and HPRT mutants were eliminated in ES cell and MEF cultures, which were then treated with EMS or left untreated as described in a. Mutation rate was calculated as previously described, but adapted for mammalian cells (13) and corrected for colony-forming efficiency. Solid bars indicate Aprt mutation rate and hatched bars represent Hprt mutation rate.…”
Section: The Spontaneous Mutation Frequency and Rate In Es Cells Are mentioning
confidence: 99%
“…Their first method used the proportion of cultures in which no mutants could be detected (P 0 ). At low mutation rates, the distribution of mutations will be approximately Poisson, with mean m. Accordingly a proportion P 0 =e 2m cultures will have no mutant colonies, and m can be estimated by 2ln(P 0 ), and the mutation rate by m/(N t 2N 0 ), where N t is the population size at time t. Although it is efficient and simple (Li & Chu, 1987), this method has drawbacks for phase variation experiments, in particular that all cells in a culture are plated and all mutants detected. The efficiency declines greatly if investigation of the whole culture is impractical (Kendal & Frost, 1988;Jones et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…It is, therefore, more common to use the median. One comparison of the methods indicated that performance decreases from maximum likelihood, the median, the upper quartile, to the mean method (Li & Chu, 1987). Each method was used to derive the parameters of the Lea & Coulson distribution from an experiment, then this distribution was compared to the actual data.…”
Section: Introductionmentioning
confidence: 99%